2004
DOI: 10.1016/j.ccr.2004.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Late viral RNA export, rather than p53 inactivation, determines ONYX-015 tumor selectivity

Abstract: ONYX-015 is an adenovirus that lacks the E1B-55K gene product for p53 degradation. Thus, ONYX-015 was conceived as an oncolytic virus that would selectively replicate in p53-defective tumor cells. Here we show that loss of E1B-55K leads to the induction, but not the activation, of p53 in ONYX-015-infected primary cells. We use a novel adenovirus mutant, ONYX-053, to demonstrate that loss of E1B-55K-mediated late viral RNA export, rather than p53 degradation, restricts ONYX-015 replication in primary cells. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
300
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(316 citation statements)
references
References 63 publications
12
300
1
1
Order By: Relevance
“…The functions of E1B 55 kDa include p53 degradation, RNA export and host protein shutoff, and the loss of these functions is an important determinant of the tumor cell selectivity of the ZD55 virus. 27 Compared with nonreplicating adenoviral vectors, ZD55 selectively replicates in tumor cells and thereby augments the spread of therapeutic gene expression. We previously have reported that ZD55-delivering therapeutic genes (for example TRAIL and IL-24) suppresses tumor growth and induces tumor cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The functions of E1B 55 kDa include p53 degradation, RNA export and host protein shutoff, and the loss of these functions is an important determinant of the tumor cell selectivity of the ZD55 virus. 27 Compared with nonreplicating adenoviral vectors, ZD55 selectively replicates in tumor cells and thereby augments the spread of therapeutic gene expression. We previously have reported that ZD55-delivering therapeutic genes (for example TRAIL and IL-24) suppresses tumor growth and induces tumor cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…32 This result was confirmed by other laboratory. 33 These two independent studies applied an E1B55K mutant R239A (ONYX-053), which produces a mutated E1B55K protein that specifically lacks the binding ability with p53. These studies demonstrated that loss of E1B55K function in inactivation of p53 or lack of E1B55K protein in dl1520 infection leads to accumulation of p53 in infected cells, as expected.…”
Section: Adenoviruses-induced Cell Cycle Changes In Hep3b and Saos2 Cmentioning
confidence: 99%
“…In addition, further studies showed that the viral RNA export functions of E1B55K is involved in viral replication and dl1520-sensitive tumor cells may provide with altered mechanisms of factors with E1B55K functions for RNA export. 33 Heat shock response rescues late viral RNA export and renders refractory tumor cells permissive to dl1520. 53 A specific question that we investigated in this study is how dl1520 can efficiently replicate in some cancer cells, but its replication is limited in other cancer cells.…”
Section: Adenoviruses-induced Cell Cycle Changes In Hep3b and Saos2 Cmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The replication of E1B-55 kDa-deleted adenovirus is severely impeded in normal cells compared with wild-type adenovirus, probably because the E1B-55 kDa protein functions in assisting late viral mRNA export from the nucleus. 3 Tumor cells can recover E1B-55 kDa function in late viral mRNA transportation to the cytoplasm. The concept of using an oncolytic virus in tumor treatment was exemplified by the development of H101, 4 a similar E1B-55 kDa-deleted type 5 adenovirus with additional deletions in the E3 region.…”
Section: Introductionmentioning
confidence: 99%